Pengaruh Model Pembelajaran Tipe Index Card Match Pada Pembelajaran Pendidikan pancasila Terhadap Hasil Belajar Kelas V UPT SPF SD Negeri Sangir Kota Makassar - Safika, Safika; Azis, Abdul; Syahrir, Musdalifah (Universitas Muhammadiyah Mataram, 2025)
This study aims to solve the problems in elementary schools related to low student learning outcomes so that the Index Card Match Type model is applied to improve student learning outcomes. This study uses a quantitative approach with a Nonequivalent Control Group Design design involving two groups, namely the control and experimental groups. The experimental group was taught with the Index Card Match model, while the control group was taught using conventional methods. Data were collected through pre-test and post-test. The results of the study showed that the average posttest score of the experimental class was higher (81) compared to the control class (69.67). There is an influence of the Index Card Match learning model on the learning outcomes of grade V students with the material of appreciating diversity in the surrounding environment at the SPF UPT SD Negeri Sangir. This is confirmed by the results of the hypothesis test with a sig value <0.001 the use of the Index Card Match learning model significantly improves student learning outcomes compared to conventional methods. The Index Card Match model is effectively applied in Pancasila Education learning to improve student learning outcomes.